Cystoid Macular Edema in Bietti's Crystalline Retinopathy - Ali Osman Saatci; Hasan Can Doruk; Aylin Yaman (Case Reports in Ophthalmological Medicine)
A 27-year-old man with progressive bilateral visual decline was diagnosed to have Bietti's crystalline dystrophy (BCD). Fluorescein angiography revealed bilateral petaloid type late hyperfluorescence implicating concurrent cystoid macular edema (CME). Optical coherence tomography exhibited cystoid foveal lacunas OU. During the follow-up of six years, intraretinal crystals reduced in amount but CME persisted angiographically and tomographically. CME is among the rare macular features of BCD including subfoveal sensorial detachment, subretinal neovascular membrane, and macular hole.